BUKUKAS APPLICATION FOR FINANCIAL REPORTING IRON CRAFTSMAN BUSINESS - Maulani, Denia; Yenti, Deni Rahma; Ayu, Diah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
For any business, recording financial statements is very important. However, economic entities that are still dominated by micro and small businesses often ignore how important the aspect of recording financial statements is. Therefore, the vision of this activity is to provide solutions to the problems felt by the people of Cibanteng Village, whose majority of the population has an iron business where the problem is their lack of awareness and knowledge in managing finances properly and appropriately. Recording simple financial statements can use the BukuKas application. The BukuKas application is a digital application that can make it easier for business actors to manage finances. The activity method used is by conducting business assistance on how important it is to make Financial Statements using the BukuKas application and digital financial literacy.